High-shrinkage chinlon production process

By blending graphene oxide or modified graphene oxide with nylon particles and melt extruding, the problem of shrinkage reduction caused by electrostatic accumulation of nylon fibers is solved, and the production of highly shrinkage nylon fibers is achieved.

CN119411241AActive Publication Date: 2025-02-11WUJIANG TIANYUAN TEXTILE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411647146.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

In the prior art, nylon fibers have a decrease in shrinkage due to electrostatic accumulation, and their shrinkage cannot be effectively improved.

Method used

A high-shrinkage nylon production process with high shrinkage is prepared by blending graphene oxide or modified graphene oxide with nylon particles and melt extruding after drying.

Benefits of technology

Using graphene oxide or modified graphene oxide as antistatic agents significantly improves the conductivity of nylon fibers, reduces electrostatic deposition, and thus significantly improves the shrinkage of nylon fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139955020000071
    Figure BDA0005139955020000071
  • Figure BDA0005139955020000081
    Figure BDA0005139955020000081
Patent Text Reader

Abstract

The invention relates to a high-shrinkage chinlon production process, and relates to the technical field of chinlon fibers. The high-shrinkage chinlon production process comprises the following steps: S1, drying chinlon particles, mixing the dried chinlon particles with an antistatic agent, and carrying out melt extrusion to obtain a spinning melt; s2, performing spinning forming on the spinning melt to obtain composite fibers, and performing stretching treatment to obtain polyamide fibers; the method has the effect of improving the contractibility of the polyamide fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nylon fibers, and in particular to a production process of high-shrinkage nylon. Background Art

[0002] Compared with polyester and acrylic, nylon has many advantages, such as strong and wear-resistant, low density, and light fabric. As a new type of textile raw material, nylon high shrinkage fiber gives nylon high shrinkage and moderate strength, which greatly broadens the application field of nylon. For example, it can be blended with conventional products into yarn, and then boiled or steamed in a tension-free state. The high shrinkage fiber curls, and the conventional fiber curls into a loop due to the constraint of the high shrinkage fiber. The yarn becomes fluffy and smooth like wool yarn, which improves the product grade and increases the variety of patterns. Therefore, the application scenarios of nylon high shrinkage fiber are very broad.

[0003] The prior art discloses a method of using co-condensing sliced ​​nylon 6 and nylon 66 as raw materials, nylon 6 accounting for 50-80wt% and nylon 66 accounting for 20-50wt%, which are sent to a screw extruder for melting, mixing, extrusion, spinning on a spinning machine, and then filtering, oiling, pre-networking, stretching, heat setting, networking, and high-speed winding to obtain nylon high-shrinkage fiber. The nylon fiber uses nylon 6 and nylon 66 as raw materials, and the nylon raw materials are prone to static electricity accumulation and mutual repulsion, thereby reducing the shrinkage of nylon. Summary of the invention

[0004] In order to improve the shrinkage of nylon fiber, the present application provides a high-shrinkage nylon production process.

[0005] The present application provides a high shrinkage nylon production process, which adopts the following technical solution: A high shrinkage nylon production process comprises the following steps: S1, drying the nylon particles, mixing the dried nylon particles with an antistatic agent and performing melt extrusion to obtain a spinning melt; S2, spinning the spinning melt to obtain composite fiber, and then stretching it to obtain nylon fiber; The antistatic agent includes graphene oxide.

[0006] By adopting the above technical solution, the nylon fiber prepared by blending the antistatic agent prepared by graphene oxide with nylon particles has excellent high shrinkage. The specific reasons are as follows: Graphene oxide has good conductivity, which can effectively improve the conductivity of nylon fiber, reduce static electricity deposition, and thus increase the shrinkage rate of nylon fiber.

[0007] Preferably, the mass ratio of the nylon particles to the antistatic agent is 1:(0.04-0.06).

[0008] By adopting the above technical solution and controlling the mass ratio of nylon particles to the antistatic agent within the above range, the electrical conductivity of nylon fibers can be effectively improved.

[0009] Preferably, the antistatic agent further comprises carbon nanotubes.

[0010] By adopting the above technical solution, firstly, the carbon nanotubes have good conductivity, so static electricity deposition can be further reduced and the shrinkage rate of nylon fibers can be further improved.

[0011] Secondly, the carbon nanotubes are curved in shape and have a large aspect ratio, which can play a connecting role between graphene oxide sheets, thereby reducing the agglomeration of graphene oxide and effectively improving the dispersibility of graphene oxide.

[0012] In addition, the mixture of graphene oxide and carbon nanotubes has a good synergistic effect when compounded with nylon particles, which can increase the compatibility between graphene oxide, carbon nanotubes and nylon particles, thereby improving the conductivity of nylon fibers, thereby further reducing the electrostatic deposition phenomenon and further improving the shrinkage rate of nylon fibers.

[0013] Preferably, the mass ratio of graphene oxide to carbon nanotubes is (5-7):1.

[0014] By adopting the above technical solution, the mass ratio of graphene oxide and carbon nanotubes is controlled within the above range, which has a positive effect on improving the shrinkage rate of nylon fibers.

[0015] Preferably, the graphene oxide is prepared by modification, and the modification preparation method of the graphene oxide comprises the following steps: Graphene oxide is added into deionized water and stirred evenly to obtain a graphene oxide dispersion; dodecylamine is added into anhydrous ethanol and stirred evenly to obtain a dodecylamine solution; the graphene oxide dispersion and the dodecylamine solution are mixed, stirred evenly, centrifuged and washed, and freeze-dried to obtain a modified graphene oxide.

[0016] By adopting the above technical scheme, graphene oxide is modified by dodecylamine, which effectively improves the interface compatibility between graphene oxide and nylon particles, increases the interlayer spacing of graphene oxide, and improves the stability of graphene oxide in the nylon matrix.

[0017] Preferably, the mass ratio of graphene oxide to dodecylamine is 1:(12-16).

[0018] By adopting the above technical solution, the mass ratio of graphene oxide and dodecylamine is controlled within the above range, which has a positive effect on improving the stability of graphene oxide in the nylon matrix.

[0019] Preferably, glycidol is further added during the graphene oxide modification process, that is, the modified preparation method of graphene oxide comprises the following steps: S100, adding graphene oxide to deionized water, stirring evenly to obtain a graphene oxide dispersion, adding dodecylamine to anhydrous ethanol, stirring evenly to obtain a dodecylamine solution, and then mixing the graphene oxide dispersion and the dodecylamine solution, stirring evenly, and then centrifuging and washing, and freeze-drying to obtain primary modified graphene oxide; S200, mixing the primary modified graphene oxide and propylene oxide, stirring evenly, introducing nitrogen gas under heating conditions and stirring to obtain a black sludge, washing the black sludge with methanol, removing the supernatant after natural precipitation, and then dialyzing the precipitate in ultrapure water, heating the precipitate, adding an ice water solution of sodium borohydride, stirring evenly, dialyzing the reaction solution in ultrapure water, and freeze-drying to obtain modified graphene oxide.

[0020] By adopting the above technical scheme, the hyperbranched polyglycerol formed by propylene oxide is connected to the surface of graphene oxide by covalent grafting. The molecular structure of the hyperbranched polyglycerol contains hydroxyl groups, which helps to improve the hydrophilicity of graphene oxide, thereby improving the hygroscopicity of nylon fibers and helping to improve the high shrinkage of nylon fibers.

[0021] Preferably, polyvinyl pyrrolidone is further added in step S1, and the specific steps of step S1 are as follows: The nylon particles are dried, and then the dried nylon particles, antistatic agent and polyvinyl pyrrolidone are mixed and melt-extruded to obtain a spinning melt; The polyvinyl pyrrolidone accounts for (2-4)% of the mass of the antistatic agent.

[0022] By adopting the above technical scheme, the ketone group in polyvinyl pyrrolidone can form hydrogen bonds and other forces with the amide group in the nylon particles, thereby generating an affinity between polyvinyl pyrrolidone and the nylon particles, and polyvinyl pyrrolidone has good wettability to the nylon particles, thereby improving the hydrophilicity of the nylon fiber and improving the shrinkage of the nylon fiber.

[0023] In addition, electrostatic force can be formed between polyvinyl pyrrolidone and carbon nanotubes, so that polyvinyl pyrrolidone has a coating effect on carbon nanotubes, improving the dispersibility of carbon nanotubes in nylon particles and further improving the conductivity of carbon nanotubes.

[0024] It also makes the surface of the carbon nanotubes more hydrophilic, improves the compatibility between the carbon nanotubes and the nylon particles, and improves the interface bonding force between the carbon nanotubes and the nylon particles, thereby improving the mechanical properties of the nylon fibers.

[0025] In addition, polyvinyl pyrrolidone can form an interface layer between carbon nanotubes and nylon particles, which has good toughness and strength, thereby dispersing stress at the interface and preventing crack propagation, thereby further improving the mechanical properties of nylon fibers.

[0026] Preferably, a metal salt is further added in step S1, and the specific steps of step S1 are as follows: The nylon particles are dried, and then the dried nylon particles, antistatic agent, polyvinyl pyrrolidone and metal salt are mixed and melt-extruded to obtain a spinning melt; The metal salt accounts for (0.5-2)% of the mass of the nylon particles.

[0027] By adopting the above technical solution, metal ions can be inserted into the nylon molecular chain, destroying the regularity of the molecular chain, reducing the crystallinity, and thus improving the shrinkage of the nylon fiber.

[0028] Preferably, the metal salt is zinc chloride.

[0029] By adopting the above technical solution, a complex can be formed between zinc chloride and polyvinyl pyrrolidone, which can enhance the stability of nylon fiber and thus improve the mechanical properties of nylon fiber.

[0030] In summary, the present application includes at least one of the following beneficial technical effects: 1. Graphene oxide has good conductivity, which can effectively improve the conductivity of nylon fiber, reduce static electricity deposition, and thus increase the shrinkage rate of nylon fiber.

[0031] 2. Carbon nanotubes have good conductivity, so they can further reduce electrostatic deposition. The mixture of graphene oxide and carbon nanotubes has a good synergistic effect with nylon particles, which can increase the compatibility between graphene oxide, carbon nanotubes and nylon particles, thereby improving the conductivity of nylon fibers, further reducing the electrostatic deposition phenomenon and further improving the shrinkage rate of nylon fibers. DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with the examples and comparative examples. The raw materials involved in the present application can be obtained commercially, among which polyvinyl pyrrolidone is provided by Hefei Tianjian Chemical Co., Ltd.

[0033] Example 1 A high shrinkage nylon production process comprises the following steps: S1, drying 100 g of nylon particles, mixing the dried nylon particles with 4 g of an antistatic agent, and then melt-extruding at 250° C. to obtain a spinning melt; S2. The spinning melt is spun into shape by a micro spinning machine to obtain composite fibers, and then passed through a hot drawing device with the heating cylinder temperature set at 120°C. Under the action of a stretching roller, the fibers are stretched 4 times to obtain nylon fibers.

[0034] The antistatic agent includes graphene oxide.

[0035] Example 2 A high shrinkage nylon production process comprises the following steps: S1, drying 100 g of nylon particles, mixing the dried nylon particles with 6 g of an antistatic agent, and then melt-extruding at 250° C. to obtain a spinning melt; S2. The spinning melt is spun into shape by a micro spinning machine to obtain composite fibers, and then passed through a hot drawing device with the heating cylinder temperature set at 120°C. Under the action of a stretching roller, the fibers are stretched 4 times to obtain nylon fibers.

[0036] The antistatic agent includes graphene oxide.

[0037] Example 3 A high shrinkage nylon production process comprises the following steps: S1, drying 100 g of nylon particles, mixing the dried nylon particles with 5 g of an antistatic agent, and then melt-extruding at 250° C. to obtain a spinning melt; S2. The spinning melt is spun into shape by a micro spinning machine to obtain composite fibers, and then passed through a hot drawing device with the heating cylinder temperature set at 120°C. Under the action of a stretching roller, the fibers are stretched 4 times to obtain nylon fibers.

[0038] The antistatic agent includes graphene oxide.

[0039] Example 4 The difference between Example 4 and Example 3 is that the antistatic agent further comprises carbon nanotubes, and the mass ratio of graphene oxide to carbon nanotubes is 5:1.

[0040] Example 5 The difference between Example 5 and Example 3 is that the antistatic agent further includes carbon nanotubes, and the mass ratio of graphene oxide to carbon nanotubes is 7:1.

[0041] Example 6 The difference between Example 6 and Example 3 is that the antistatic agent further includes carbon nanotubes, and the mass ratio of graphene oxide to carbon nanotubes is 6:1.

[0042] Example 7 The difference between Example 7 and Example 6 is that the graphene oxide is prepared by modification, and the modification preparation method of the graphene oxide comprises the following steps: 1 g of graphene oxide was added to 100 g of deionized water and stirred evenly to obtain a graphene oxide dispersion; 12 g of dodecylamine was added to 150 g of anhydrous ethanol and stirred evenly to obtain a dodecylamine solution, and then the graphene oxide dispersion and the dodecylamine solution were mixed, stirred at 25°C for 24 hours, and then centrifuged with a mixture of deionized water and anhydrous ethanol (the mass ratio of deionized water to anhydrous ethanol was 1:1), and freeze-dried to obtain modified graphene oxide.

[0043] Example 8 The difference between Example 8 and Example 6 is that the graphene oxide is prepared by modification, and the modification preparation method of the graphene oxide comprises the following steps: 1 g of graphene oxide was added to 100 g of deionized water and stirred evenly to obtain a graphene oxide dispersion; 16 g of dodecylamine was added to 150 g of anhydrous ethanol and stirred evenly to obtain a dodecylamine solution, and then the graphene oxide dispersion and the dodecylamine solution were mixed, stirred at 25°C for 24 hours, and then centrifuged with a mixture of deionized water and anhydrous ethanol (the mass ratio of deionized water to anhydrous ethanol was 1:1), and freeze-dried to obtain modified graphene oxide.

[0044] Example 9 The difference between Example 9 and Example 6 is that the graphene oxide is prepared by modification, and the modification preparation method of the graphene oxide comprises the following steps: 1 g of graphene oxide was added to 100 g of deionized water and stirred evenly to obtain a graphene oxide dispersion; 14 g of dodecylamine was added to 150 g of anhydrous ethanol and stirred evenly to obtain a dodecylamine solution, and then the graphene oxide dispersion and the dodecylamine solution were mixed, stirred at 25°C for 24 hours, and then centrifuged with a mixture of deionized water and anhydrous ethanol (the mass ratio of deionized water to anhydrous ethanol was 1:1), and freeze-dried to obtain modified graphene oxide.

[0045] Example 10 The difference between Example 10 and Example 9 is that the mass ratio of graphene oxide to dodecylamine is 1:10.

[0046] Embodiment 11 The difference between Example 11 and Example 9 is that the mass ratio of graphene oxide to dodecylamine is 1:18.

[0047] Example 12 The difference between Example 12 and Example 9 is that glycidol is further added during the graphene oxide modification process. The modified preparation method of graphene oxide comprises the following steps: S100, adding 1g of graphene oxide to 100g of deionized water, stirring evenly, to obtain a graphene oxide dispersion; adding 14g of dodecylamine to 150g of anhydrous ethanol, stirring evenly, to obtain a dodecylamine solution, and then mixing the graphene oxide dispersion and the dodecylamine solution, stirring at 25°C for 24h, and then centrifuging with a mixed solution of deionized water and anhydrous ethanol (the mass ratio of deionized water to anhydrous ethanol is 1:1), and freeze-drying to obtain primary modified graphene oxide; S200. After mixing 100 mg of primary modified graphene oxide and 25 L of propylene oxide, stir evenly, and then introduce nitrogen at 140° C. and stir for 24 hours to obtain a black sludge. The black sludge is then ultrasonically washed 3 times with 300 L of methanol. After natural precipitation, the supernatant is removed and the mixture is heated to 75° C., and 10 g of an ice-water solution of sodium borohydride (the mass concentration of the ice-water solution of sodium borohydride is 4%) is added dropwise to the solution. Stirring is continued for 3 hours, and the reaction solution is dialyzed in ultrapure water for 3 days to obtain an aqueous solution of hyperbranched polyglycerol-modified graphene. After freeze-drying, modified graphene oxide is obtained.

[0048] Embodiment 13 The difference between Example 13 and Example 12 is that polyvinyl pyrrolidone is further added in step S1.

[0049] That is: S1, 100g of nylon particles are dried, and then the dried nylon particles, 3g of antistatic agent and polyvinyl pyrrolidone are mixed and melt-extruded at 250°C to obtain a spinning melt.

[0050] Polyvinyl pyrrolidone accounts for 2% of the mass of the antistatic agent.

[0051] Embodiment 14 The difference between Example 14 and Example 13 is that the polyvinyl pyrrolidone accounts for 4% of the mass of the antistatic agent.

[0052] Embodiment 15 The difference between Example 15 and Example 13 is that polyvinyl pyrrolidone accounts for 3% of the mass of the antistatic agent.

[0053] Example 16 The difference between Example 16 and Example 15 is that a metal salt is further added in step S1.

[0054] That is: S1, 100g of nylon particles are dried, and then the dried nylon particles, 3g of antistatic agent, polyvinyl pyrrolidone and metal salt are mixed and melt-extruded at 250°C to obtain a spinning melt.

[0055] The metal salt accounts for 0.5% of the mass of the nylon particles, and the metal salt is zinc chloride.

[0056] Embodiment 17 The difference between Example 17 and Example 16 is that the metal salt accounts for 2% of the mass of the nylon particles.

[0057] Embodiment 18 The difference between Example 18 and Example 16 is that the metal salt accounts for 1.2% of the mass of the nylon particles.

[0058] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no antistatic agent is added during the production process of the high shrinkage nylon.

[0059] Performance testing: The nylon fibers obtained in Examples 1-18 and Comparative Example 1 were sampled (samples of equal length), boiled at the same temperature for 30 minutes, taken out and dried, and the lengths of the three samples were measured after balancing for 2 hours, and the boiling water shrinkage was calculated, boiling water shrinkage = (sample length before boiling - sample length after boiling) / sample length before boiling * 100%, and the results are recorded in Table 1.

[0060] Table 1 Data analysis Specifically combining the test results of Examples 4-6 and Example 3, the shrinkage of Example 4-6 is better than that of Example 3. The analysis is as follows: the difference between Example 4-6 and Example 3 is that the antistatic agent contains carbon nanotubes in addition to graphene oxide. On the one hand, the carbon nanotubes have good conductivity. On the other hand, the carbon nanotubes can reduce the agglomeration of graphene oxide and increase the compatibility between graphene oxide, carbon nanotubes and nylon particles, thereby improving the conductivity of nylon fibers, reducing electrostatic deposition, and further improving the shrinkage of nylon fibers.

[0061] Specifically combining the test results of Examples 7-9 and Example 6, the shrinkage of Example 7-9 is better than that of Example 6. The analysis is as follows: the difference between Example 7-9 and Example 6 is that the graphene oxide is modified by dodecylamine, which improves the interface compatibility between the graphene oxide and the nylon particles, thereby improving the stability of the graphene oxide in the nylon matrix, and then improving the shrinkage of the nylon fiber.

[0062] Specifically combining the test results of Example 12 and Example 9, the shrinkage of Example 12 is better than that of Example 9. The analysis is as follows: the difference between Example 12 and Example 9 is that propylene oxide is also added during the graphene oxide modification process, which improves the hydrophilicity of the graphene oxide, thereby improving the hygroscopicity of the nylon fiber, and then improving the shrinkage of the nylon fiber.

[0063] Specifically combining the test results of Examples 13-15 and Example 12, the shrinkage of Examples 13-15 is better than that of Example 12. The analysis is as follows: the difference between Examples 13-15 and Example 12 is that polyvinyl pyrrolidone is also added during the preparation of nylon fiber. On the one hand, polyvinyl pyrrolidone can improve the shrinkage of nylon fiber, and on the other hand, it can improve the conductivity and hydrophilicity of carbon nanotubes, thereby improving the shrinkage of nylon fiber.

[0064] Specifically combining the test results of Examples 16-18 and Example 15, the shrinkage of Examples 16-18 is better than that of Example 15. The analysis is as follows: the difference between Examples 16-18 and Example 15 is that metal salts are also added during the preparation process of nylon fibers, which can effectively reduce the crystallinity, thereby improving the shrinkage of nylon fibers.

[0065] Specifically combining the test results of Example 1 and Comparative Example 1, the shrinkage of Example 1 is better than that of Comparative Example 1. The analysis is as follows: the difference between Example 1 and Comparative Example 1 is that graphene oxide is added during the preparation of nylon fiber. Graphene oxide has good conductivity, which can effectively improve the conductivity of nylon fiber and reduce electrostatic deposition, thereby improving the shrinkage rate of nylon fiber.

[0066] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high shrinkage nylon production process, characterized in that: The steps include: S1, drying the nylon particles, mixing the dried nylon particles with an antistatic agent and performing melt extrusion to obtain a spinning melt; S2, spinning the spinning melt to obtain composite fiber, and then stretching it to obtain nylon fiber; The antistatic agent includes graphene oxide.

2. A high shrinkage nylon production process according to claim 1, characterized in that: The mass ratio of the nylon particles to the antistatic agent is 1:(0.04-0.06).

3. A high shrinkage nylon production process according to claim 2, characterized in that: The antistatic agent also includes carbon nanotubes.

4. A high shrinkage nylon production process according to claim 3, characterized in that: The mass ratio of the graphene oxide to the carbon nanotubes is (5-7):

1.

5. The high shrinkage nylon production process according to claim 1, characterized in that: The graphene oxide is prepared by modification, and the modification preparation method of the graphene oxide comprises the following steps: Graphene oxide is added into deionized water and stirred evenly to obtain a graphene oxide dispersion; dodecylamine is added into anhydrous ethanol and stirred evenly to obtain a dodecylamine solution; the graphene oxide dispersion and the dodecylamine solution are mixed, stirred evenly, centrifuged and washed, and freeze-dried to obtain a modified graphene oxide.

6. A high shrinkage nylon production process according to claim 5, characterized in that: The mass ratio of the graphene oxide to dodecylamine is 1:(12-16).

7. A high shrinkage nylon production process according to claim 6, characterized in that: Glycidol is also added in the graphene oxide modification process, that is, the modification preparation method of graphene oxide comprises the following steps: S100, adding graphene oxide to deionized water, stirring evenly to obtain a graphene oxide dispersion, adding dodecylamine to anhydrous ethanol, stirring evenly to obtain a dodecylamine solution, and then mixing the graphene oxide dispersion and the dodecylamine solution, stirring evenly, and then centrifuging and washing, and freeze-drying to obtain primary modified graphene oxide; S200, mixing the primary modified graphene oxide and propylene oxide, stirring evenly, introducing nitrogen gas under heating conditions and stirring to obtain a black sludge, washing the black sludge with methanol, removing the supernatant after natural precipitation, and then dialyzing the precipitate in ultrapure water, heating the precipitate, adding an ice water solution of sodium borohydride, stirring evenly, dialyzing the reaction solution in ultrapure water, and freeze-drying to obtain modified graphene oxide.

8. A high shrinkage nylon production process according to claim 4, characterized in that: The step S1 is further added with the following specific steps: The nylon particles are dried, and then the dried nylon particles and the antistatic agent are mixed and melt-extruded to obtain a spinning melt; The amount of the antistatic agent is (2-4) % by weight.

9. A high shrinkage nylon production process according to claim 8, characterized in that: Metal salt is also added in step S1, and the specific steps of step S1 are as follows: The nylon particles are dried, and then the dried nylon particles, antistatic agent, and metal salt are mixed and melt-extruded to obtain a spinning melt; The said accounts for (0.5-2)% of the mass of the nylon particles.

10. A high shrinkage nylon production process according to claim 9, characterized in that: The metal salt is zinc chloride.

Citation Information

Patent Citations

  • Hygroscopic fine denier / superfine denier nylon masterbatch, nylon and preparation method thereof

    CN101747624A

  • Graphene and multiwalled carbon nanotube synergetic enhanced polymer fiber and preparation method thereof

    CN104357941A

  • Preparation method of military anti-dripping anti-static high-tenacity flame-retardant polyester

    CN105177753A

  • Preparation method of compound conductive fibers

    CN106012093A

  • Preparation method of high-shrinkage fiber

    CN106637480A